2018
DOI: 10.1021/acs.molpharmaceut.8b00816
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Transfer Learning and Multitask Learning Approach for Pharmacokinetic Parameter Prediction

Abstract: Note: Zhuyifan Ye and Yilong Yang made equal contribution to the manuscript. ABSTRACT:Background: Pharmacokinetic evaluation is one of the key processes in drug discovery and development.However, current absorption, distribution, metabolism, excretion prediction models still have limited accuracy.Aim: This study aims to construct an integrated transfer learning and multitask learning approach for developing quantitative structure-activity relationship models to predict four human pharmacokinetic parameters. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 74 publications
(114 reference statements)
0
59
0
Order By: Relevance
“…The multitask (MT) learning technique has achieved much success in qualitative Merck and Tox21 prediction challenges. [45][46][47][48] In the MT framework, multiple tasks share the same hidden layers. However, the output layer is attached to different tasks.…”
Section: Iid Multitask Deep Neural Network (Mt-dnn)mentioning
confidence: 99%
“…The multitask (MT) learning technique has achieved much success in qualitative Merck and Tox21 prediction challenges. [45][46][47][48] In the MT framework, multiple tasks share the same hidden layers. However, the output layer is attached to different tasks.…”
Section: Iid Multitask Deep Neural Network (Mt-dnn)mentioning
confidence: 99%
“…More recently, there have been promising applications of AI methods to ADMET prediction. For example, the recent use of transfer and multitask learning in predicting pharmacokinetic parameters [38] or the application of DL to ADMET prediction [39]. Moreover, public-private partnerships such as the eTOX consortium have been created to recover legacy toxicological data from big pharmaceutical companies and develop better predictive models [40].…”
Section: Admet Modellingmentioning
confidence: 99%
“…Zhuyifan et al developed an integrated transfer learning and multitask learning approach to predict pharmacokinetic parameters for small molecule drugs on the market. 13 Compared with other machine learning approaches, Yilong et al demonstrated that deep learning methods can achieve the highest accuracy to predict the in vitro performances of pharmaceutical formulations. 14 Run et al established a prediction model for the disintegration time of oral disintegrating tablets, and the model achieved 80% accuracy.…”
Section: Introductionmentioning
confidence: 99%